Papr Performance Analysis For Combination Of Selective Mapping (Slm) And Exponential Companding Technique - Oh, Meng Hui (Universiti Sains Malaysia, 2017)
OFDM was a multicarrier transmission scheme that increase data transmission rate. However, OFDM has high PAPR problem which can cause signal distortion. A PAPR reduction scheme known as SLM-Exp was introduce in this project to overcome high PAPR problem of OFDM. To evaluate the PAPR performance of SLM-Exp, SLM-Exp scheme along with SLM-Mu and Exponential were simulated in MATLAB for PAPR value at 1×10−3 of CCDF plot. PAPR performance of SLM-Exp was compare with SLM-Mu, and Exponential scheme as number of subcarrier, phase sequence and modulation scheme varied. The number of subcarrier concern in this project were 64, 128, 256, and 512. Number of phase sequence concern in this project were 8, 16 and 32. For modulation scheme, QPSK, 16 QAM, and 64 QAM were concern in this project. The result shows that PAPR value of SLM-Exp at 1×10−3 of CCDF plot was better than SLM-Mu by 0.53dB to 2.31dB and 0.10dB to 0.61dB for Exponential scheme as number of subcarrier varied. Result also shows that PAPR performance of SLM-Exp is better than SLM-Mu by 0.99dB to 1.63dB as number of phase sequence varied.